EFFECT OF CLITORIA TERNATEA ON FOLLICULOGENESIS POLYCISTIC OVARY SYNDROME: IN SILICO STUDY ON LUTEINIZINNG HORMONE RECEPTOR - Kurniawati, Erna Yovi; Muhlida, Vinilia Ihramatul (Yayasan Healing and Healthcare Education, 2025)
Polycystic Ovary Syndrome (PCOS) is a complex hormonal disorder involving dysregulation of luteinizing hormone (LH) and its receptor, leading to menstrual irregularities and anovulation. This study evaluates the potential of Clitoria ternatea, a traditional medicinal plant, in modulating LH receptor activity through in silico analysis. Methods: Active compounds from Clitoria ternatea, including flavonols (kaempferol, isorhamnetin), flavones (baicalein, luteolin, apigenin), phenolic acids (chlorogenic, protocatechuic, gallic), and epicathechin, were identified via PubChem. Lipinski’s rule and LD50 classifications were used to assess drug-like properties and toxicity. Bioactivity was predicted using PASS Online, SwissTarget Prediction, PharmMapper, and SuperPred. The LH receptor's 3D structure was modeled using Swiss Model and validated with Procheck and Errat Check. Molecular docking studies using PyRx assessed binding affinities between the compounds, spironolactone, flutamide, and the LH receptor. Results: Docking results revealed strong binding affinities of Clitoria ternatea compounds with the LH receptor, particularly phenolic acids and flavonoids, showing comparable or better interactions than spironolactone and flutamide. These interactions suggest a potential role in restoring hormonal balance and ovulatory function. The study highlights the therapeutic potential of Clitoria ternatea for PCOS management. Its compounds demonstrate significant LH receptor interactions, offering a promising basis for further research. Conclusion: Clitoria ternatea shows promise as a natural therapeutic candidate for PCOS. Future in vitro, in vivo, and clinical trials are needed to validate these findings